REKONSTRUKSI JARGON FORMALISASI SYARIAT: UPAYA MENJAGA PERSATUAN DALAM BINGKAI KEBERAGAMAN - Lufaefi Lufaefi (UIN Raden Mas Said Surakarta, 2017)
This paper discusses the urgency of reconstructing idea on the formalization of Islamic sharia and the future of Indonesia. Formalization of Islamic law which is proposed by Islamic fundamentalist group as the solution of the various problems faced by the people living in the nation-state context needed should be contextualized with the reality of Indonesia as the plural country. By using critical analysis approach on the various argument of the fundamentalist group, which then contextualize with the reality of diversity in Indonesia, revealed that formalization of Islamic sharia is not a solution. Khilafah system will not be able to be forced to be implemented in Indonesia. Interpretation of the text about politics and government must be taken serious attention to be reviewed. In the history of the implementation of Islamic government and Islamic ideology as implemented by the Prophet Muhammad PbUH in Arab is really different with the Indonesian background which is plural.Â Â Â